Pyrophyllite dissolution at elevated pressure conditions: An ab initio study. (15th August 2021) - Schliemann, René; Churakov, Sergey V.
Abstract: The atomistic mechanism of dissolution reactions at mineral fluid interface is essential for understanding the reaction kinetics and the adsorption and thermodynamic equilibria at mineral surfaces. In this study we investigate the initial state of the dissolution process on (0 1 0) surface of pyrophyllite at elevated pressure by applying large-scale ab initio Meta-Dynamics simulations. The system setup provides a realistic representation of the clay mineral edge surface structure and takes into account explicit dynamics of solvent molecules. The model parameters follow the procedure recently tested for the simulation of the (1 1 0) pyrophyllite edge. The simulation reveals that dissolution of a single tetrahedral or an octahedral unit from the clay mineral edge is a complex multi-step process with several reaction intermediates. Typically, each reaction step changes the denticity of the reacting site in a step-by-step manner and leads, eventually, to the leaching of the ions forming the octahedral and tetrahedral sheets of the phyllosilicate. The solvent rearrangement and the proton transfer reactions in the first and second coordination shell of the dissolving unit play a critical role in the stabilization of reaction intermediates and the net progress of the dissolution reactions. In contrast to ambient conditions, the transition complexes formed during the dissolution at elevated conditions were found to have an increased coordination number. The simulation reveals new insight into the coordination environment of the dissolving complexes at the mineral fluid interface.